2018
DOI: 10.35229/jaes.429761
|View full text |Cite
|
Sign up to set email alerts
|

Türkiye Çanakkale İlinde Pammene gallicolana (Lepidoptera, Tortricidae)’nın İlk Kaydı ve Türün Dış ve Genital Morfolojisi

Abstract: This study was conducted in the field and the laboratory. Pammene gallicolana was caught in various fruit orchards in light trap and pheromone trap in Çanakkale. In the field studies, totally 23 male and 18 female specimens were collected. Specimens were dissected and male genitalia and wing microscope slides were prepared in the laboratory. We described both the external and genital morphology of the male Pammene gallicolana and diagnostic morphological features in detail. As a result of the study, Pammene ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…The diamondback moth is a severe pest and recently distributed some regions in Turkey. Therefore, studies that will provide sufficient information about its biology, laboratory rearing on its host and/or artificial diet are crucial (Avcı and Ozbek, 1995;Atay et. al., 2019;Saran and Genç, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The diamondback moth is a severe pest and recently distributed some regions in Turkey. Therefore, studies that will provide sufficient information about its biology, laboratory rearing on its host and/or artificial diet are crucial (Avcı and Ozbek, 1995;Atay et. al., 2019;Saran and Genç, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The diamondback moth (DBM), Plutella xylostella (L.) (Lepidoptera: Plutellidae), is a worldwide pest of brassica vegetable and oilseed crops (Scarisbrick and Daniels, 1986;Shahidi, 1990;Talekar and Shelton, 1993;Capinera, 2002;Raymer, 2002;Mosiane et al, 2003;Wilkerson et al, 2005;Furlong et al, 2008;Zalucki et al, 2012;Furlong et al, 2013;Saran and Genç, 2021). Adults are 12-13 mm long with fringed wings and brown (Talekar and Shelton, 1993;Capinera, 2002;Atay et. al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The diamondback moth is known as the oligophagous and feeds on Brassicaeous plants that contain glycosides known as phagostimulants (Gupta and Thorsteinson, 1960;Golizadeh et al, 2009). In Turkey, it was first reported in Artvin, Murgul district in 1965 (Alkan, 1965) then Avcı and Özbek (1990) reported the diamondback moth in Brassicaeous cultuvated areas in Erzurum and recently Atay et al (2019) was reported the pest in Çanakkale province.…”
Section: Introductionmentioning
confidence: 99%